Beyond the divide : a century of Canadian mosque design - Gaber, Tammy (Montreal ; Kingston ; London ; Chicago : McGill-Queen's University Press, 2022)
"Canada's first mosque, the Al Rashid mosque in Edmonton, was built in 1938. In the years since, as Canada's Muslim population has grown, close to two hundred mosques, Islamic centres, prayer spaces, and Jamatkhanas have been built across the country. Beyond the Divide explores the mosques of Canada in their diversity, beauty, practicality, and versatility. Tracking the country from east to west and to the north, Tammy Gaber visits ninety mosques in more than fifty cities, including Canada's most northern places of worship in Nunavut and the North West Territories. For nearly a century Muslims have made mosques in a variety of spaces, from converted shops and vacated churches to large, purpose-built complexes. Drawing on site photographs, architectural drawings, and interviews, Gaber explores the extraordinary diversity in how these spaces have been designed, built, and used--as places not only of worship, but of community gathering, education, charitable work, and civic engagement. Throughout, Beyond the Divide provides a groundbreaking analysis of gendered space in Canadian mosques, how these spaces are designed and reinforced, and how these divides shape community experience. The first comprehensive study of mosque history and architecture in Canada, Beyond the Divide reveals the mosque to be a dynamic building type that adapts to its context, from its climate and physical environment to the community it serves. Above all, mosque designs depend on the people who gather in them, and what those people aspire for their mosques to be."--
Introduction: The Mosque in Canada -- Pioneering Communities and Mosques in the Prairies -- The Potential of Converted Spaces in Quebec Mosques -- The Promise of Purpose-Built Mosques in British Columbia -- Mosques as Hubs of Community Space in the Maritimes -- Orienting Mosques to Mecca in Canada and the Extreme North -- Women and the Gendering of Mosques in Ontario -- Conclusion: Trends and Trajectories in Canadian Mosques
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 28, 2025).
eBooks on EBSCOhost
Keywords: Mosques -- Canada -- Design and construction -- History; Mosques -- Canada -- History; Islamic architecture -- Canada -- History; Mosques as community centers -- History; Architecture islamique -- Canada -- Histoire; Mosquées (Centres communautaires) -- Histoire; ARCHITECTURE / Buildings / Religious; Islamic architecture; Mosques; Mosques as community centers; Mosques -- Design and construction; Canada; Al Rashid; Canadian; Edmonton; Islam; Ismaili; Jamatkhana; Masjid Al Salaam; Noor; Room; architecture; charity; cube; declaration; epigraphy; fasting; gathering; mihrab; mosque; muslim; pilgrimage; prayer spaces; qibla; research creation; shahada; typology; women; worship; History